Imperial power and popular politics : class, resistance and the state in India, c. 1850-1950 - Chandavarkar, Rajnarayan (Cambridge ; New York : Cambridge University Press, 1998)
In this series of interconnected essays, Rajnarayan Chandavarkar offers a powerful revisionist analysis of the relationship between class and politics in India between the Mutiny and Independence. Dr Chandavarkar rejects the 'Orientalist' view of Indian social and economic development as exceptional and somehow distinct from that prevailing in capitalist societies elsewhere, and reasserts the critical role of the working classes in shaping the pattern of Indian capitalist development. Sustained in argument and elegant in exposition, these essays represent a major contribution not only to the history of the Indian working classes, but to the history of industrial capitalism and colonialism as a whole. Imperial Power and Popular Politics will be essential reading for all scholars and students of recent political, economic, and social history, social theory, and cultural and colonial studies.--Publisher description.
1. Introduction -- 2. Industrialization in India before 1947: conventional approaches and alternative perspectives -- 3. Workers, trade unions and the state in colonial India -- 4. Workers' politics and the mill districts in Bombay between the wars -- 5. Workers, violence and the colonial state: representation, repression and resistance -- 6. Police and public order in Bombay, 1880-1947 -- 7. Plague panic and epidemic politics in India, 1896-1914 -- 8. Indian nationalism, 1914-1947: Gandhian rhetoric, the Congress and the working classes -- 9. South Asia and world capitalism: towards a social history of labour.
Includes bibliographical references (pages 351-376) and index.
Print version record.
Keywords: Capitalism -- India -- History -- 19th century; Capitalism -- India -- History -- 20th century; Working class -- India -- History -- 19th century; Working class -- India -- History -- 20th century; Social classes -- India -- History -- 19th century; Social classes -- India -- History -- 20th century; Imperialism -- History; BUSINESS & ECONOMICS -- Free Enterprise; Capitalism; Imperialism; Social classes; Working class; India; Imperialisme; Sociaal-economische ontwikkeling; Arbeidersklasse; Kapitalisme; 1800-1999; Electronic books; History; India